The Influence of Organizational Culture, Competence, and Work Environment on Job Satisfaction and Employee Performance - Rizqi, Muhamad; Riyadi, Slamet; Nugroho, Riyadi (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This research was designed to determine the influence of organizational culture, competency and work environment on job satisfaction and employee performance at PT Ciomas Adisatwa in Sidoarjo Regency. This research data comes from a questionnaire distributed to 75 respondents. To prove the Research Hypothesis. So the data analysis technique used is the Partial Least Squere (PLS) method. Research Results Show that Organizational Culture has an effect of 0.271 on Job Satisfaction, Competency has an effect of 0.359 on Job Satisfaction, Work Environment has an effect of 0.236 on Job Satisfaction, Job Satisfaction has an effect of 0.408 on employee performance, Organizational Culture has an effect of 0.159 on employee Performance, Competence has an effect of 0.265 on employee performance, the work environment has an effect of 0.200 on employee performance.